Prevalence of and risk factors for hazardous drinking and alcohol use disorders among married men in the Wattala divisional secretarial area. - De Silva, E.J.M.P (My University, 2006)
Objective of the study was to translate, adapt and validate the AUDIT 10-item questionnaire and to determine prevalence of and risk factors for hazardous drinking (HZD) land alcohol use disorders (AUD) among married men. The risk factors for HZD and AUD were determined under personal, family and environmental domains. For HZD the reference group was LRD while for AUD it was HZD. Binary logistic regression analyses were performed to determine independent effects of risk factors after controlling for confounding effects. Restricting accessibility to both illicit and licit alcohol is strongly recommended while improving accessibility to alternate recreational services at the same time. Replacing pro-drinking attitudes with pro-healthy attitudes is a sustainable effective strategy, which could be introduced, in family settings. Provision of services on improving coping skills, screening and management of symptoms of anxiety and depression among married men is an effective strategy in preventing progression of HZD in to AUD